Marital Choice in Arab Societies: Methods and Standards (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
In this research, we dealt with the concept of marital choice and its most important methods used in our Arab societies, such as the arranged parenting style and the free, self- and cooperative, restricted style. Such as homogeneity theory, normative theory, needs integration theory, spatial juxtaposition theory, ideal partner theory, psychoanalytic theory, and parental image theory. The research concluded with a summary and recommendations regarding the elements of positive choice and the mechanisms for their support.